STABILITY EVALUATION OF CREAM EXTRACT OF NEEM, GOTU KOLA AND SOURSOP FOR DERMATITIS TREATMENT IN DOG - Suartha, I Nyoman; Sudimartini, Luh Made; Wijayanti, Ni Putu Ayu Dewi (Buletin Veteriner Udayana, 2021)
This study aims to evaluate the stability of herbal extract creams with a combination of neem leaves, gotu kola, and soursop extract to cure dermatitis complex in dogs., This herb extract has been able to inhibit in vitro the growth of bacteria that cause dermatitis. This research was conducted in the Laboratory of Non-Sterile Formulation and Technology at the Department of Pharmacy, Faculty of Mathematics and Natural Sciences, Udayana University. Cream preparations were made in three formulations; each formulation was evaluated for stability at room temperature. Evaluation of the stability of cream includes organoleptic test, homogeneity test, pH test, adhesion test, spreadability test, and viscosity test. The results showed the cream was stable at room temperature for one month and the stable formula was formula 1. It can be concluded that the herb of formula 1 extract cream was stable at room temperature for one month.